Study on Drainage of Pavement Layers and Improvement Strategies: Case Study - Hosein Zanjirani Farahani; Atiye Farahani (Journal of Rehabilitation in Civil Engineering)
Road infrastructure facilities have a crucial role in the development of countries by providing connectivity of cities for humans and goods. Moisture intrusion is one of the main pavement damages that can decline the pavement surface conditions and reduce structural strength and load-carrying capacity. The design of the pavement layers needs to collect data about soil properties, regional precipitation, pavement geometries, surface and subsurface drainage properties, and vehicular traffic. In this study, the drainage of the pavement layers of Qom-Kashan Freeway (Amirkabir Freeway) located in Iran has been investigated. In experimental studies, the classification, physical and chemical properties, Atterberg limits and Sand Equivalent (SE),‌ density and moisture of the pavement layers,‌ the load-bearing capacity of the pavement layers materials, and drainage system quality have been evaluated. The classification of materials is mostly of the type (GW-GM) A-1-a and (GP-GM) A-1-b, which are suitable materials for the implementation of the subgrade, sub-base, and base layers. The percentage of weight loss of materials of the sub-base and base layers, with Los Angeles and sodium sulfate abrasion tests, is within the allowable limits. Results of the test of Atterberg limits determination of the pavement layers indicate that most of the materials in the subgrade, sub-base, and base layers are non-plastic (NP). So, the problem of swelling is not observed in these layers. To prevent water permeation into the pavement body, destruction of the bottom layers, and pumping the paving materials, four strategies have been suggested and applied to improve the drainage performance.